2012
DOI: 10.5152/tud.2012.030
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless PNL in the supine position

Abstract: Objective: To evaluate the safety, feasibility and efficacy of tubeless percutaneous nephrolithotomy (PNL) in a supine position in selected cases with renal stones. Materials and methods:This descriptive study enrolled 120 patients who presented to the urology department at Benha Faculty of Medicine with renal stones between June 2009 and June 2010. All patients were evaluated based on their history, a physical examination, kidney, ureter, bladder (KUB), pelviabdominal U/S and spiral CT of the abdomen and pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Other studies reported mean operative times ranging between 67.1±19.2 and 78.93±3.8 minutes with tubeless supine PCNL. [20,21] In our study (Table 4) only 2 (3.7%) patients received blood transfusion which is comparable to available literature indicating requirement for blood transfusion in 2.5-4% of the relevant patients. [12,20] Regarding Two (3.7%) patients developed complication of perinephric collection which was managed conservatively.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Other studies reported mean operative times ranging between 67.1±19.2 and 78.93±3.8 minutes with tubeless supine PCNL. [20,21] In our study (Table 4) only 2 (3.7%) patients received blood transfusion which is comparable to available literature indicating requirement for blood transfusion in 2.5-4% of the relevant patients. [12,20] Regarding Two (3.7%) patients developed complication of perinephric collection which was managed conservatively.…”
Section: Discussionsupporting
confidence: 88%
“…Forty-six (86.7%) patients were managed by inferior calyceal puncture which is at higher rates compared to relevant reports in the literature ranging between 72 and 70.8 percent. [12,20] Overall mean operative time was 57±12.3 minutes (range:34-90 minutes). For tubeless and totally tubeless PCLs mean operative times were 62.91±11.9, and 52.50±10.7 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies reported mean operative time of around 67.1 ± 19.2 and 78.93 ± 3.8 min with tubeless supine PCNL. 21,24 We achieved complete clearance in single stage in 93.7% of cases. Two cases were postponed because of blood on the initial puncture.…”
Section: Discussionmentioning
confidence: 87%